RANCANGAN BOOKLET BIOLOGI KELAS X SMA PADA MATERI BAKTERI DAN JAMUR - Deya ayudia Mesrayanti; Zulfarina Zulfarina; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of booklet design in class X bacterial high school learning material. This research was conducted at the Binawidya Riau University in March- Mei 2020. This research was conducted in 2 stages: the experimental stage and the second stage is Booklet Design that is analysis of the potential development of high school learning media Bacteria and Fungi class X material. The study used an experimental method of descriptive qualitative research design. Based on the potential analysis, it was found that endophytic bacteria isolated from Laban plants can be used as a booklet design of class X bacterial material for SMA KD 3.5 and fungi material KD 3.7.Key Words: Bacteria, Booklet, Fungi